Les enceintes fortifiées du Limousin Les habitats protohistoriques de la France non méditerranéenne - Ralston, Ian B. M. (Documents d'archéologie française, 1992)
What is known about the settlement sites of non-Mediterranean Gaul at the end of the Iron Age? Relatively little compared to our knowledge of contemporary sites near the Mediterranean littoral. This study, based on a regional inventory of the settlement sites of Limousin, is a contribution to filling that gap. The author considers archaeological, numismatic and historical data from Corrèze, Creuse and Haute-Vienne in relation to information from other regions of France, and proposes an analysis of Gaulish society and political structures in the immediately pre-Conquest period. The study is avowedly regionalist in perspective and offers a critique of earlier, brooder- scale models of change during this period.